Shewanella infection in humans: Epidemiology, clinical features and pathogenicity. Issue 1 (31st December 2022) - Yu, Keyi; Huang, Zhenzhou; Xiao, Yue; Wang, Duochun
ABSTRACT: The genus Shewanella consists of Gram-negative proteobacteria that are ubiquitously distributed in environment. As the members of this genus have rapidly increased within the past decade, several species have become emerging pathogens worldwide, attracting the attention of the medical community. These species are also associated with severe community- and hospital-acquired infections. Patients infected with Shewanella spp. had experiences of occupational or recreational exposure; meanwhile, the process of infection is complex and the pathogenicity is influenced by a variety of factors. Here, an exhaustive internet-based literature search was carried out in PUBMED using terms " Achromobacter putrefaciens, " " Pseudomonas putrefaciens, " " Alteromonas putrefaciens " and " Shewanella " to search literatures published between 1978 and June 2022. We provided a comprehensive review on the epidemiology, clinical features and pathogenicity of Shewanella, which will contribute a better understanding of its clinical aetiology, and facilitate the timely diagnosis and effective treatment of Shewanella infection for clinicians and public health professionals.